Comparative Performance Islamic Shares Mutual Funds Between Indonesia And Malaysia - Basuki, Novianto; Khoiruddin, Moh (Universitas Muhammadiyah Ponorogo, 2018)
The objective of this study is to evaluate the performance of Islamic mutual funds in Indonesia and Malaysia. Research conducted on the types of shares mutual funds in the period 2014 until 2016. The technique sample used was purposive sampling method with 13 Islamic mutual funds in Indonesia and 72 Islamic mutual funds in Malaysia. Fund performance measured by Sharpe index, Treynor index, and Index of jenesen’s Alpha. The results of this study showed in 2014 and 2016 Islamic mutual fund performance be superior to Indonesia than Malaysia. While in 2015 Islamic mutual fund performance Malaysia be superior compared to Indonesia. Based on the results of this research, it is recommended for investment managers to increase the publication of and understanding of mutual funds so that more potential investors who are interested in investing in mutual funds in particular Islamic mutual funds.